Peroxide route to the synthesis of ultrafine CeO2-Fe2O3 nanocomposite via successive ionic layer deposition. Issue 3 (March 2019) - Popkov, V.I.; Tolstoy, V.P.; Nevedomskiy, V.N.
Abstract: An ultrafine α-CeO2 –α-Fe2 O3 nanocomposite was prepared from the ultradispersed nanoparticles of cerium (IV) and iron (III) amorphous hydroxides heat-treated at 600 °С and 900 °С in the air. The initial composites were obtained by the successive ionic layer deposition (SILD) method. According to scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and powder X-ray diffraction (PXRD), the cerium/iron ratio in the synthesized nanocomposite is close to 1:2, and the α-CeO2 and α-Fe2 O3 nanocrystals are isometrically shaped and have an average size of 4 ± 1 and 7 ± 1 nm (600 °С) and 24 ± 2 and 35 ± 3 nm (900 °С), respectively. Transmission electron microscopy (TEM) and selected area electron diffraction (SAED) have shown that nanocrystals are evenly distributed in the composite volume and are spatially conjugated. The formation mechanisms of both initial amorphous composites of cerium (IV) and iron (III) hydroxides and of α-CeO2 and α-Fe2 O3 nanocrystals were established. It was shown that synthesis of the initial hydroxide composite using the SILD method proceeds via the formation of amorphous cerium hydroxo-peroxide (CeO(OOH)2 ). As a result of the study, a schematic mechanism for the formation of a composite based on ultrafine nanocrystals of cerium (IV) and iron (III) oxides has been proposed.